IMPACT OF VIRTUAL LEARNING ENVIROMENTS ON STUDENTS MATHEMATICAL PERFORMANCE - Hafedh Taher, Dr. Nedhal Abdul (International Journal of Advanced Science and Technology, 2019)
The study aims to measure the impact of virtual learning environment on mathematical performance in higher education institutions in Kurdistan Region of Iraq from the faculty members and students viewpoints, and to indicate if there are significant differences between the studies variables.Descriptive analytical approach is adopted; a questionnaire for collecting datais designed, distributed among three dimensions i.e. teaching, learning and evaluation.The questionnaire met the requirements of validity, reliability and consistency.The study showed that the degree of the impact ofvirtuallearning environmentVLE on student’s mathematical performance in the overall the three dimensions is above than the theoretical mean.The study went out with a set of recommendations to those in charge of mathematics education in universities, to initiate training the faculty members of mathematics in education technology through organizing workshops, scientific symposia, and through exploits advantages provided by e-learning in connecting the theories in mathematics with its practical applications.